Crosses of two independently derived transgenic mice demonstrate functional complementation of the genes encoding heavy (HLA-B27) and light (beta 2-microglobulin) chains of HLA class I antigens. - Krimpenfort, P (1987)
In man a number of diseases are associated with certain alleles of MHC antigens. The most pronounced example is ankylosing spondylitis, which is strongly associated with HLA-B27. As a first step towards a model system to study the basis of this association, transgenic mice were generated that showed cell surface expression of the HLA-B27 antigen biochemically indistinguishable from HLA-B27 antigen expressed on human cells. This result was obtained by crossing two independently derived strains of mice, one of which is transgenic for the HLA-B27 heavy chain gene, and the other carrying and expressing the human beta 2m gene. Examination of HLA-B27 and human beta 2m mRNA in various tissues shows the two genes to be expressed in a coordinate fashion. The mRNA levels follow those of endogenous H-2 Class I genes.